Development of Interactive Web-Based Media on Outer Space and the Solar System in Grade 6 Elementary School IPAS Learning to Measure Students' Learning Outcomes - Clarissa Shelsa Dila; Azmi Al Bahij (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study is motivated by the limited availability of instructional media in elementary schools, which encourages the need for innovations in the development of learning resources. The problem addressed in this research is the lack of interactive, web-based media for science learning, particularly on the topic of space and the solar system for sixth-grade elementary school students. The objective of this study is to develop an interactive web-based instructional medium and to evaluate its effectiveness in improving students’ learning outcomes in Science (IPAS) learning. This research applied a Research and Development (R&D) approach using the ADDIE development model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research sample involved 20 sixth-grade students from Mawar Class at SD Perjuangan Terpadu Depok. The product produced in this research is an interactive web-based learning media on space and the solar system, created through Google Sites and equipped with learning materials and interactive features. The results indicate that the interactive web-based media is suitable for classroom use and has a positive impact on students' learning outcomes. The product’s effectiveness was measured through pretest and posttest scores, analyzed using a paired t-test, which yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant improvement. The N-Gain analysis showed a value of 0.79, categorized as high. Therefore, it can be concluded that the developed media effectively enhances students’ learning outcomes. The findings are expected to be beneficial for school principals, teachers, parents, students, and future researchers.